1994
DOI: 10.1128/iai.62.8.3543-3546.1994
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of surface alpha-1,3-glucan in genetically related strains of Blastomyces dermatitidis that differ in virulence

Abstract: Recent studies of the dimorphic fungal pathogens Histoplasma capsulatum and Paracoccidioides brasiliensis have suggested a role in virulence for the cell surface carbohydrate a-(1,3)-glucan. To investigate a possible basis for a-(1,3)-glucan in the pathogenicity and virulence of the dimorphic fungus Blastomyces dermatitidis, we examined three genetically related strains of B. dermatitidis that differ in their virulence for mice: wild-type virulent strain ATCC 26199; mutant strain ATCC 60915, which is 10,000-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(54 citation statements)
references
References 14 publications
0
52
0
2
Order By: Relevance
“…In B. dermatitidis, the conversion from mold to yeast results in an increased cell wall content of α-(1,3)-glucan and a decreased β-(1,3)-glucan content [8]. In the pathogenic yeast forms of several of the dimorphic fungi, including B. dermatitidis, H. capsulatum and P. brasiliensis, the level of α-(1,3)-glucan in the cell wall correlates with the level of virulence [9]. Additionally, as cells adapt to changes in temperature, multiple changes occur in the lipid composition of the plasma membrane, which leads to remodeling and reorganization of the membrane [10].…”
Section: Yeast Phase Specific Factors and Their Role In Virulencementioning
confidence: 99%
“…In B. dermatitidis, the conversion from mold to yeast results in an increased cell wall content of α-(1,3)-glucan and a decreased β-(1,3)-glucan content [8]. In the pathogenic yeast forms of several of the dimorphic fungi, including B. dermatitidis, H. capsulatum and P. brasiliensis, the level of α-(1,3)-glucan in the cell wall correlates with the level of virulence [9]. Additionally, as cells adapt to changes in temperature, multiple changes occur in the lipid composition of the plasma membrane, which leads to remodeling and reorganization of the membrane [10].…”
Section: Yeast Phase Specific Factors and Their Role In Virulencementioning
confidence: 99%
“…(2007) has presented evidence that α‐1,3‐glucan masks β‐glucan on the cell wall of Histoplasma capsulatum to block host recognition of the fungal invasion. A correlation between reduction in α‐1,3‐glucan and virulence has also been observed in other dimorphic fungal pathogens, such as Paracoccidioides brasiliensis and Blastomyces dermatitidis (San‐Blas et al ., 1977; Hogan and Klein, 1994; Rappleye and Goldman, 2006). Similarly to the case of H. capsulatum , it has been assumed that the fungal α‐1,3‐glucan conceals cell wall MAMPs on the fungal cell surface to circumvent recognition by hosts (Hogan et al ., 1996; Rappleye and Goldman, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, down-regulated genes specific of dimorphism in the , 1997); it is known that this morphological change is accompanied by a change in the chemical composition of the cell wall. For example, in P. brasiliensis, Blastomyces dermatitidis, and Histoplasma capsulatum, it was demonstrated that the levels of a-1,3-glucans are directly related to the levels of virulence (Hogan & Klein, 1994). The composition of the cell wall of the yeast and mycelial forms of U. maydis showed differences both qualitative and quantitative.…”
Section: Analysis Of the Differentially Expressed Genes Specific Of Dmentioning
confidence: 99%